Effect of indoor climbing on heart rate among climbers-beginners and advanced climbers - stress load - Culková, D.; Špás, D.; Šinkovský, R. (Journal of Outdoor Activities, 2013)
The presented study examines the issue of stress load when climbing on artificial walls. This matter is shown on example of heart rate levels in case of climbers-beginners and advanced climbers. The target group are the beginners and advanced climbers whose heart rate, through the load curve and the factors, points to the actual load, which affects the individual climber. Based on the record of the heart rate and the questionnaires a partial objective was also the analysis of the differences examined from several perspectives.